Onset and duration of ejaculatory suppression effect of tamsulosin in goat - Kimsakulvech, Sakdichod; Suttiyotin, Peerasak; Pinyopummin, Anuchai (Agriculture and Natural Resources, 2016)
The duration of ejaculatory suppression of alpha adrenoceptor antagonist (tamsulosin, TAM) was investigated in goats. Five males were injected intramuscularly with TAM 80 mg/kg (179.8 nmol/kg). Semen was collected using an artificial vagina with estrous female goats and the semen quality and libido score were evaluated at 1, 3, 6 and 9 h post TAM injection. Two replicates were carried out in the study. Heart rates were also measured before the injection and at 30 min before semen collection. The results showed that the libido score was not affected by TAM. At 1 h post injection, the highest percentage of suppressed ejaculation (80%) was recorded and this effect was maintained for up to 3 h post injection (60%). Thereafter the percentage of suppressed ejaculation was significantly decreased (p < 0.05) at 6 h (20%) and ejaculation was completely recovered at 9 h post injection. The semen characteristics of the collectable semen, semen volume and number of spermatozoa were lowest at 1 h and 3 h, thereafter they suddenly increased at 6 h and the significantly highest peak was noted at 9 h post injection. TAM injection suppressed goat ejaculation within 1 h and the duration was maintained up to 3 h post injection.